Analýza deformací povrchu rotoru turbodmychadla v místě radiálního ložiska - Tabukashvili, Giorgi (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2025)
Rotory turbodmychadel jsou vystaveny vysokému tepelně-mechanickému zatížení. Práce se zaměřuje na turbodmychadlo desetiválcového stacionárního spalovacího motoru s an výkon 1,6 MW. V místech radiálních ložisek pod nimi dochází k významným deformacím rotoru chod turbodmychadla, a to především z důvodu nerovnoměrného rozložení teplot. Tyto deformace mít za následek změnu tvaru mazací mezery ložiska. Práce se zabývá hodnocením deformace v místě radiálního ložiska v ustáleném stavu při současném provozu působení tepelného zatížení a mechanického zatížení v důsledku předpětí a rotace. Přesněji řečeno Cílem je přehled deformací rotoru turbodmychadla při termomechanickém zatížení. Podle analýza teplotního pole rotoru v místě radiálního ložiska za ustáleného provozu. A analýza deformace povrchu rotoru v místě radiálního ložiska v ustáleném stavu operace.

The rotors of turbochargers are subjected to high thermal–mechanical loads. The work focuses on the turbocharger of a ten–cylinder stationary internal combustion engine with an output of 1.6 MW. Significant rotor deformations occur at the journal bearing locations under turbocharger operation, mainly due to uneven temperature distribution. These deformations result in a change in the shape of the bearing lubrication gap. The work deals with the evaluation of the deformation at the journal bearing location in steady state operation under simultaneous application of thermal load and mechanical load due to preload and rotation. More precisely the goal is to Review of turbocharger rotor deformations under thermo–mechanical loading. By analyzing the rotor temperature field at the journal bearing location under steady state operation. And analyzing the rotor surface deformation at the journal bearing location under steady state operation.
Analysis of surface deformations of the turbocharger rotor at the location of the radial bearing
Keywords: Heat transfer; turbocharger; FEM; radial bearing.; Heat transfer; turbocharger; FEM; radial bearing.